2008
DOI: 10.1177/0887403408315442
|View full text |Cite
|
Sign up to set email alerts
|

The Prison Rape Elimination Act (PREA)

Abstract: Although the Prison Rape Elimination Act (PREA) is an acknowledgment of problems posed by forcible sexual assault in prisons and jails, many institutions of confinement at various levels of government continue to struggle with developing compliant policies and procedures. Given this practical reality, the purpose of this article is twofold. First, the authors examined the policies of 28 states plus the Federal Bureau of Prisons ( n = 29) to assess the extent to which they comply with federal law using eight ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The efficacy of PREA as a mechanism of rape prevention in carceral facilities is difficult to ascertain. Of the notably few empirical analyses on the topic, prior research has quantitatively examined individual and/or structural predictors of prison violence without explicitly accounting for PREA compliance (Hensley et al, 2003; Listwan et al, 2014; Morash et al, 2012; Wolff et al, 2009), predictors of PREA compliance but not policy efficacy (Thompson et al, 2008), and chronological patterns in reported prevalence using national survey data that are unable to account for unreported crimes (see Smith, 2020). This body of research has unearthed evidence of individual risk factors associated with abuse risks, such as being young, small in stature, poorly educated, a racial minority, a history of mental illness, a history of childhood sexual victimization, and recently entering the prison system (Hensley et al, 2003; Listwan et al, 2014; Morash et al, 2012; Wolff et al, 2009; see also Sutton and Sutton, 2016) as well as structural risk factors, including the safety of the prison environment and attitudes regarding corrections officers (Listwan et al, 2014).…”
Section: Prea Overview and Prior Assessmentsmentioning
confidence: 99%
“…The efficacy of PREA as a mechanism of rape prevention in carceral facilities is difficult to ascertain. Of the notably few empirical analyses on the topic, prior research has quantitatively examined individual and/or structural predictors of prison violence without explicitly accounting for PREA compliance (Hensley et al, 2003; Listwan et al, 2014; Morash et al, 2012; Wolff et al, 2009), predictors of PREA compliance but not policy efficacy (Thompson et al, 2008), and chronological patterns in reported prevalence using national survey data that are unable to account for unreported crimes (see Smith, 2020). This body of research has unearthed evidence of individual risk factors associated with abuse risks, such as being young, small in stature, poorly educated, a racial minority, a history of mental illness, a history of childhood sexual victimization, and recently entering the prison system (Hensley et al, 2003; Listwan et al, 2014; Morash et al, 2012; Wolff et al, 2009; see also Sutton and Sutton, 2016) as well as structural risk factors, including the safety of the prison environment and attitudes regarding corrections officers (Listwan et al, 2014).…”
Section: Prea Overview and Prior Assessmentsmentioning
confidence: 99%
“…Another major objective of PREA was to improve reporting procedures (PREA, 2003). In particular, many states adopted mandatory reporting practices for all staff who witness or are informed of a sexual assault, in addition to a telephone hotline that is set up for the reporting of such incidents (Thompson et al, 2008). In an effort to improve reporting practices, many states mandated formal training for correctional staff on detecting and reporting sexual assaults.…”
Section: Legislative Response To Sexual Assault In Prisonsmentioning
confidence: 99%
“…The seriousness of this type of sexual victimization prompted the passage of the Prison Rape Elimination Act (PREA, 2003) in the United States which mandated states develop strategies to identify, collect, and report data related to the occurrence of sexual assault in confinement facilities. PREA also provided a structure to detect and report sexual assaults with the goals of protecting victims and implementing swift institutional responses (e.g., zero-tolerance sexual assault policies; PREA, 2003; Thompson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although this created movement toward creating a safer environment for trans women who are incarcerated, critiques of these changes include that it is often the only policy in place that provides any type of explicit guidance regarding working with this population but is not intended to serve this purpose (Sevelius and Jenness, 2017). Further, multiple lawsuits have been filed by trans women who are incarcerated in PREA-compliant prisons (Thompson et al, 2008) indicating that PREA as a stand-alone policy is not enough to safeguard incarcerated trans women (Sexton et al, 2010). Maycock's (2022) qualitative research on the experiences of transgender people incarcerated in Scotland supports the idea that formalized policies intended to reduce the vulnerabilities of transgender people do not necessarily provide clear pathways to safety and inclusion.…”
Section: The Correctional Context and Gendermentioning
confidence: 99%